Sosialisasi CIKUR (Ciri-Ciri Keaslian Rupiah ) Tahun Emisi 2016 untuk Menghambat Peredaran Uang Palsu dalam Penerimaan Dana Sumbangan di Masjid Al Irsyad Kertonegoro Kecamatan Jenggawah Kabupaten Jember - Dimas Herliandis Shodiqin (Mujtama': Jurnal Pengabdian Masyarakat, 2021)
Money is one of the most important things in carrying out economic activities. Considering this, BI always updates the security of Rupiah currency in effort to provide security and comfort for the public, this is because people themselves are still careless about seeing the authenticity of Rupiah in cash transactions. This, therefore, can open up opportunities for counterfeit money crimes that are very detrimental for the society, including the use of Rupiahs in the process of receiving donations or social funds at the mosque. In this service, in collaboration with the Jember Branch of BI Office, a campaign on CIKUR (Characteristics of Authentic Rupiah currency) TE 2016 at the Al Irsyad Kertonegoro Mosque, Jenggawah, Kabupaten Jember was carried out. The objectives of this service are: to provide socialization related to CIKUR TE 2016 to educate the public regarding complaints of receiving counterfeit money at BI's Jember Branch, provide tips on caring for Rupiah currency, and exchange money unfit for circulation at BI. The method used is the demonstration method related to CIKUR TE 2016. The results of this dedication are that the public can know the characteristics of authentic Rupiah currency. Also, the public is aware of the counterfeit money complaint process handled by the Jember BI Branch. The public knows how to protect and treat counterfeit money, and currency exchange is not fit for circulation. the public knows the characteristics of authentic Rupiah currency. the public is aware of the counterfeit money complaint process handled by the Jember BI Branch. The public knows how to protect and treat counterfeit money, and currency exchange is not fit for circulation. the public knows the characteristics of authentic Rupiah currency. The public is aware of the counterfeit money complaint process handled by the Jember BI Branch. The public knows how to protect and treat counterfeit money, and currency exchange is not fit for circulation.